Associations between proposed local government liquor store size classifications and alcohol consumption in young adults. (July 2018) - Foster, Sarah; Hooper, Paula; Knuiman, Matthew; Lester, Leanne; Trapp, Georgina
Abstract: The prevalence of warehouse-style liquor stores has prompted alarm from local communities and public health advocates. To increase local government control over liquor stores, one proposed planning response is to distinguish between 'small' (i.e., ≤ 300 m 2 ) and 'large' (i.e., > 300 m 2 ) liquor stores. We mapped the size and location of liquor stores in Perth, Western Australia, and tested associations between liquor store exposure and alcohol consumption (grams ethanol/day) in young adults (n = 990). The count of liquor stores of any size within 1600 m and 1601–5000 m of home were significantly associated with increased alcohol intake, whereas larger stores (i.e., > 300 m 2 and > 600 m 2 ) were not associated with alcohol intake. Young adults' alcohol consumption appears to be impacted by liquor store density and convenience, rather than outlet size. However, the presence of multiple stores close to home increases market competition, driving alcohol prices down, and plausibly results in alcohol prices similar to those at liquor superstores. Highlights: The number of warehouse-style discount liquor stores in Australia is increasing. One local government planning response is to classify and restrict stores by size. We tested whether liquor store size was associated with alcohol consumption. Number of stores was associated with alcohol intake, but not stores > 300 m 2 or > 600 m 2 . Liquor store density and convenience appear key to alcohol intake in young people.